Tinjauan Kelengkapan dan Keakuratan Pengisian Resume Medis Pasien Rawat Inap pada Ruangan Paru di BLUD RSU Ratu Zalecha Martapura Tahun 2012 - Irmawan Irmawan; Apit Widiarta; Rian Hidayatullah; STIKES Husada Borneo (HB PRESS, 2013)
Completeness and accuracy of resume filing medical inpatients in the lung’s room in BLUD RSU Ratu Zalecha Martapura there is still a form of medical resume incomplete and inaccurate contents so greatly influence the information needs of patients and in a report prepared by the hospital. The purpose of this study was to determine the completeness of medical resume charging patients hospitalized on the pulmonary room, knowing the accuracy of resume charging medical inpatients at room Knowing factor ng and factors that affect the completeness and accuracy of resume charging medical inpatients at room lungs. This type of survey research is descriptive method with quantitative approach, data collection and conduct interviews conducted by review of inpatient medical records room filled lung. The samples were 123 medical inpatients resume on lung room. The results indicate medical resume charging the completeness of data on the identification of 80,21%, 13,23% critical reports, authentication and recording 66,66% are either 100% do not use coretandan type-x. The accuracy of medical resume charging the identification data of 77,50%, 11,85% critical report, authenticated 65,05%, and a good record 100% accurate. Human resources (HR) at Hospital BLUD RSU Ratu Zalecha Martapura mainly assembling already plays an important part of the completeness of medical records but the constraints of the charging current is D3 because they are not medical records so it is difficult to understand how the actual provisions of the comprehensiveness and accuracy of medical resume. Doctors have a special room facilities are available, after providing direct care to patients physicians complete medical records of patients in the room. Assembling parts already using Standard Operating Procedure (SOP) in 2010 but has not been going well.